Clinical, morphological and immunohistochemical findings in canalicular adenoma - Silva, Leorik Pereira da; Silva, Luiz Arthur Barbosa da; Silveira, Éricka Janine Dantas da; Oliveira, Patrícia Teixeira de; Miguel, Márcia Cristina da Costa (Journal of Oral Diagnosis, 2017)
Canalicular adenoma (CAd) is an uncommon benign salivary gland tumor, usually located in the upper lip. We carried out a survey of cases of CAds among the all salivary gland tumors submitted to an Oral Pathology service over a 36-year period, and performed a comprehensive literature review of all CAds reported from 2006 to 2016. Among 161 salivary gland tumors, only two were diagnosed as CAds. A detailed clinical, morphological and immunohistochemical (IHC) study of the two cases was performed. Morphologically, the tumors were characterized by cuboidal to columnar neoplastic cells lining cystic spaces and forming tumor cords. The IHC reactions (positive for cytokeratin-7, AE1/ AE3, S-100, p63, and negative for α-SMA) supported a luminal/ductal cell proliferation without myoepithelial cells. The clinical features of the cases were similar to that shown in the literature, while the morphological and IHC findings confirmed the epithelial nature of the tumor, and highlighted important differential diagnostic aspects.